2012
DOI: 10.5830/cvja-2012-050
|View full text |Cite
|
Sign up to set email alerts
|

Role of four-week resistance exercise in preserving the heart against ischaemia-reperfusion-induced injury : cardiovascular topic

Abstract: ObjectiveWe studied the cardioprotective effect of resistance training against ischaemia–reperfusion-induced injury.MethodsForty male rats were divided into trained and sedentary groups (n = 20 for each). The trained rats were exercised at 12 repetitions/set, four sets/day and five days/week for four weeks. Transient regional ischaemia of the left anterior descending coronary artery (40 min) was followed by 80 min of reperfusion.ResultsBaseline developed and diastolic pressures and coronary flow were similar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…A previous study by Doustar et al ( 17 ), using another RT model (climbing a vertical ladder), showed that 4 weeks of RT did not preserve the heart against ischemia-reperfusion injury, evidenced by no change in the infarct size. Quinteiro et al ( 23 ) showed that only eight weeks of dynamic aerobic exercise training, but not RT (climbing a vertical ladder), was able to attenuate systolic and diastolic dysfunction in postmenopausal rats with diabetes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A previous study by Doustar et al ( 17 ), using another RT model (climbing a vertical ladder), showed that 4 weeks of RT did not preserve the heart against ischemia-reperfusion injury, evidenced by no change in the infarct size. Quinteiro et al ( 23 ) showed that only eight weeks of dynamic aerobic exercise training, but not RT (climbing a vertical ladder), was able to attenuate systolic and diastolic dysfunction in postmenopausal rats with diabetes.…”
Section: Discussionmentioning
confidence: 91%
“…Our group has previously characterized the cardiovascular adaptations of this type of exercise in animal models, such as concentric ventricular hypertrophy without LV internal chamber reduction and the participation of AT1R, decreased resting BP and improved single LV myocyte function ( 12 15 ). Other groups have used the same model to study the influence of RT on bone mass and insulin resistance, and as non-pharmacological therapy for the treatment of ischemia-reperfusion-induced injury ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the present investigation is one of the first studies to have measured I/R‐injury in resistance exercised animals with T1DM. Doustar et al ( 2012 ) examined the impact of a 4‐week resistance training program on I/R‐injury in healthy rats and reported no exercise‐related benefits. However, in a subsequent study it was demonstrated that 12 weeks of resistance training led to significant improvements in coronary flow, developed pressure, diastolic pressure, and infarct size, suggesting that this form of exercise can be effective for cardiac protection (Soufi et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, two studies have investigated the potential benefit of resistance exercise training on cardioprotection in rodents. While one study concluded that resistance training does not result in cardioprotection (32), another investigation, using a longer duration (i.e., 12 wk) of resistance training, showed that resistance training can result in a small, but significant, level of defense against IR-induced myocardial infarction (134). Obviously, additional studies are required to substantiate the influence of resistance training on cardioprotection.…”
Section: Exercise-induced Cardioprotectionmentioning
confidence: 99%